Assessment of Risk Predisposition to Human Papilloma Virus through Cervical Infections Screening of Women Attending an Outpatient Health Facility In Nairobi, Kenya - Omire, Agnes; Budambula, Nancy; Ochieng, Washingtone; Baliach, Caroline; Kerosi, Danvas; Langat, Hillary; Okemwa, Minda; Kirumbi, Leah; Aman, Rashid; Ogutu, Bernhardts; Lwembe, Raphael (My University, 2014)
There is limited data on comparative disposition to cervical cancer among HPV infected women in Kenya. We aimed to determine the distribution of HPV infection, cervical abnormalities and infections commonly reported on cervical pap smears among both HIV positive and HIV negative women attending a reproductive health clinic at the largest national hospital in Kenya. A total of 187 women aged 18 to 50 years attending the reproductive clinic at Kenyatta National Referral Hospital in Nairobi were recruited into the study. All consenting subjects were screened for HIV by serology and their cervical smears taken and immediately fixed on slides for Papanicolaou (Pap) staining. A second endocervical swab was collected in the same sitting for HPV DNA extraction and PCR amplification of the HPV LI region. Of the 187 women studied, 27 (14.4 %) were positive for HIV and 90 (48.1%) had one or more infection associated with bacterial vaginosis, candidiasis, cervicitis or inflammation of the cervix of unknown cause. Eight (4.3%) women had abnormal cervix, 3/8 being of high grade squamous intraepithelial lesions (HSIL), 1/8 of low grade squamous intraepithelial lesions (LSIL), 1/8 had adenocarcinoma while the remaining 3 had atypical squamous cells of undetermined significance (ASC-US). The remaining 89/187 (47.6%) women had normal smears with no infection. Of the 89 women with normal smears, 82 (92.1%) were HIV negative. A total of 66 (35.3%) women were positive for HPV L1 DNA by PCR and included 30 of the 89 women with normal cytology. Of the 27 HIV positive women, 14 (51.9%) were also positive for HPV LI DNA. 52 of the 160 (32.5%) HIV negative women were positive for HPV L1 DNA. We report more cases of cervical intraepithelial lesions among HIV positive than HIV negative women. Similarly, the other infections commonly found on Pap smear tests were higher among HIV negative than HIV positive women. HPV prevalence among these clinic-attending women was higher in those with normal cytology, indicating an increased underlying risk of cervical cancer in a setting where routine diagnostic screening is limited or non-existent.
Keywords: cervical cancer; HIV; HPV; cervical cytology